Marlojong sebelum Perkawinan: Kiat Adat Menghadapi Wali ‘Aḍal di Ranah Batahan, Pasaman Barat - Salma Salma; Syahril Syahril (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
This article aims to analyze and explore the tradition of marlojong before marriage in Ranah Batahan, West Pasaman. Marlojong is the act of a couple who is not approved by their parent (wali) for certain reasons by running to the house of the elder of custom (tetua adat) or a respected family. The elopement could reduce the dignity of women and their parents. So, it becomes a reason for the traditional elders to call them. The data was collected by observation and in-depth interviews with couples who did marlojong, parents of each couple, other nuclear families, traditional elders, KUA officials and local scholars. The data was analyzed by reduction, display and verification. The results showed that the meaning of marlojong was actually not only a couple who fled to the house of the traditional elders but also the efforts to overcome the guardian's reluctance (wali ‘aḍal) and reduce the parobanan (brideprice). Therefore, the causes of marlojong were overcoming the reluctant of parents and the high level of brideprice. On one side, the marlojong was seen as negative but on the other hand, it became a customary way to resolve the guardian’s reluctance (wali ‘aḍal) without having to go to a religious court.